2012
DOI: 10.1111/j.1462-2920.2012.02839.x
|View full text |Cite
|
Sign up to set email alerts
|

An extensive investigation into the prevalence and the genetic and serological diversity of toxigenic Vibrio parahaemolyticus in Italian marine coastal waters

Abstract: Summary The relationship between Vibrio parahaemolyticus strains isolated from the aquatic environment and those isolated from cases of infection in humans is poorly understood due to the low prevalence of tdh‐ and/or trh‐positive strains in the environment. To address this concern, it would be useful to analyse the genetic relationships among environmental and food strains and with reference to clinical isolates, also applying molecular typing methods. The aim of this study was to evaluate the prevalence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
4
22
0
1
Order By: Relevance
“…There are few reports of foodborne infections caused by trh-positive strains, but infections caused by tdh-positive V. parahaemolyticus are common. Therefore, information regarding seafood contaminated with trh-positive strains is limited in the world ( Johnson et al, 2010;Nakaguchi, 2013;Ottaviani et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…There are few reports of foodborne infections caused by trh-positive strains, but infections caused by tdh-positive V. parahaemolyticus are common. Therefore, information regarding seafood contaminated with trh-positive strains is limited in the world ( Johnson et al, 2010;Nakaguchi, 2013;Ottaviani et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…This is of concern as approximately half the reported foodborne cases in Asian countries are caused by V. parahaemolyticus (Alam et al, 2002; Bhuiyan et al, 2002). Frequent outbreaks of V. parahaemolyticus cases have also been reported in the United States and coastal countries of Europe such as Spain, Italy, and Norway (Caburlotto et al, 2008; Scallan et al, 2011; Ottaviani et al, 2013). …”
Section: Virulence Factors Of Vibrio Parahaemolyticusmentioning
confidence: 99%
“…T3SS1 is prevalent in all V. parahaemolyticus strains, whereas T3SS2 is more popular among clinical isolates (Meador et al, 2007). Comparative genomic analysis of pre-pandemic and pandemic V. parahaemolyticus strains, as well as molecular profiling studies, revealed that the organization of mobile gene cassettes and pathogenicity islands were divergent in these V. parahaemolyticus strains and that the emergence of pandemic strain could be associated with the recombination events and novel gene acquisition (Hurley et al, 2006; Gonzalez-Escalona et al, 2008; Han et al, 2008; Caburlotto et al, 2011; Chen et al, 2011; Yan et al, 2011; Garcia et al, 2012; Gennari et al, 2012; Gavilan et al, 2013; Ottaviani et al, 2013; Theethakaew et al, 2013; Turner et al, 2013). The genetic divergence of V. parahaemolyticus strongly correlates with their diverse virulence potentials (Vongxay et al, 2008; Caburlotto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%